Preparing future teachers to prevent the negative impact of information and telecommunications technologies on secondary school students - Дмітренко, Н. Є. (Educational Dimension, 2021)
In the article the problem of preparation of future teachers to prevention of negative influence of information and telecommunication technologies on the students of comprehensive school is examined; essence of negative influence of information and telecommunication technologies on the students of comprehensive school are lighted up.